Perspectives on Micro(Nano)Plastics in the Marine Environment: Biological and Societal Considerations - Soares, Joana (2020)
Marine litter is a global problem which has been negatively a ecting the environment. Plastic materials are the most commonly found marine debris, with potential biological (not only for aquatic organisms but also for humans) as well as socio-economic impacts. Considering that it is an anthropogenic problem, society could play an important role to minimize it. Although a considerable amount of research has addressed the biological e ects of plastics (micro(nano)plastics) on biota, few studies have addressed how scientific information is being transmitted to the public and the potential role of citizen environmental education. The current paper discusses known e ects, researched topics and how scientific knowledge is currently being transmitted to the public.